Luminous model of the cardiac conduction system. - Tovar O., Adolfo; Kabela, E.; Cabello, O.; Valenzuela, F. (Revista Mexicana de Ingenieria Biomedica, 1988)
We present a luminous model of the process of propagation of the electrical signal of the heart that exemplifies the sequence of activation of cardiac conduction pathways, as well as its relationship with the electrocardiogram. The system is based on an educational microcomputer (MKE-Z60), which controls a matrix array of LEDs, which are arranged in a way that resembles the main elements that make up the heart, and that through ordered sequences of information, can present the electric flow that circulates thought.